Intracranial Carotid Calcification on Cranial Computed Tomography. Issue 9 (September 2015) - Subedi, Deepak; Zishan, Umme Sara; Chappell, Francesca; Gregoriades, Maria-Lena; Sudlow, Cathie; Sellar, Robin; Wardlaw, Joanna
<x xml:space="preserve">Abstract</x> Background and Purpose— Intracranial internal carotid artery calcification is associated with cerebrovascular risk factors and stroke, but few quantification methods are available. We tested the reliability of visual scoring, semiautomated Agatston score, and calcium volume measurement in patients with recent stroke. Methods— We used scans from a prospective hospital stroke registry and included patients with anterior circulation ischemic stroke or transient ischemic stroke whose noncontrast cranial computed tomographic scans were available electronically. Two raters measured semiautomatic quantitative Agatston score, and calcium volume, and performed qualitative visual scoring using the original 4-point Woodcock score and a modified Woodcock score, where each image on which the internal carotid arteries appeared was scored and the slice scores summed. Results— Intra- and interobserver coefficient of variations were 8.8% and 16.5% for Agatston, 8.8% and 15.5% for calcium volume, and 5.7% and 5.4% for the modified Woodcock visual score, respectively. The modified Woodcock visual score correlated strongly with both Agatston and calcium volume quantitative measures (both R2=0.84; P<0.0001); calcium volume increased by 0.47-mm/point increase in modified Woodcock visual score. Intracranial internal carotid artery calcification increased with age by all measures (eg, visual score, Spearman ρ=0.4; P=0.005). Conclusions— Visual scores correlate highly with quantitative intracranial internal carotid artery calcification measures, with excellent observer agreements. Visual intracranial internal carotid artery scores could be a rapid and practical method for epidemiological studies.